Pembuatan Hidrolisat Ikan Rucah Sebagai Penyedap Rasa Alami dengan Memanfaatkan Enzim Bromelin pada Buah Nanas (Ananas comosus) - Ulfatul Mardiyah; Ismi Jasila; Devi Arianty (Faculty of Science and Technology University Ibrahimy, 2024)
Producing protein hydrolysates from trash fish is important to increase the added value and utilization of trash fish itself. The hydrolysis process of trash fish is carried out enzymatically using the enzyme bromelain to produce peptide chains and umami amino acids such as glutamic acid. The aim of this research was to determine the effect of variations in the addition of bromelain enzymes to pineapple fruit on glutamic acid levels, organoleptic properties, and the proximate content of trash fish hydrolyzate as a natural flavoring. The design of this research was an experimental study using a completely randomized design (CRD) with levels of pineapple extract and bromelain enzyme addition of 10%, 15%, and 20%. The results of soluble protein testing and organoleptic tests were carried out using analysis of variance (ANOVA). Further testing uses the Duncan test. to determine the best treatment using the effectiveness index test. The results of organoleptic testing of trash fish hydrolyzate show that differences in pineapple juice concentration (bromelain enzyme) of 10% (P1), 15% (P2), and 20% (P3) have a significant effect on consumer acceptability based on taste and aroma attributes. Meanwhile, the color attributes of trash fish hydrolyzate did not differ significantly between treatments. The highest monosodium glutamate content was found in the third treatment (P3; 20%). The water content, ash content, fat content, and protein content of the trash fish hydrolyzate with the best treatment (P3; 20%) were respectively 95.11%, 6.50%, 3.44%, and 82.06%.